2007
DOI: 10.1634/theoncologist.12-11-1321
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Hepatocellular Carcinoma in Asia

Abstract: After completing this course, the reader will be able to:1. Discuss the selection criteria of patients with hepatocellular carcinoma for liver transplantation.2. Describe the problems associated with the application of liver transplantation for hepatocellular carcinoma and the possible solutions.3. Discuss the current status of liver transplantation for hepatocellular carcinoma in Asia.Access and take the CME test online and receive 1 AMA PRA Category 1 Credit ™ at CME.TheOncologist.com CME CME With the promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 85 publications
1
102
0
1
Order By: Relevance
“…However, the availability of organs limits access to this best curative therapy. The annual incidence of deceased organ donors does not exceed 5 per million in most Asian countries [9] . Compared with those in Western countries, patients with HCC in Asia have a low probability of receiving a deceased donor liver transplantation (DDLT) in a timely manner and thus have a higher risk of drop-out because of tumor progression [10] .…”
Section: Surgical Therapiesmentioning
confidence: 99%
“…However, the availability of organs limits access to this best curative therapy. The annual incidence of deceased organ donors does not exceed 5 per million in most Asian countries [9] . Compared with those in Western countries, patients with HCC in Asia have a low probability of receiving a deceased donor liver transplantation (DDLT) in a timely manner and thus have a higher risk of drop-out because of tumor progression [10] .…”
Section: Surgical Therapiesmentioning
confidence: 99%
“…The incidence of HCC varies according to geographic location due to various geographic exposure to hepatitis viruses. Asia, in that sense, is considered a high-incidence region with high frequency of hepatitis B virus (4). Liver transplantation is theoretically the best oncologic treatment for HCC by removing the tumor with the widest margin and curing the background cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…1 The first liver transplant in Asia was performed in 1964 by Nakayama in Chiba, Japan with a graft from a non-heart-beating donor. This was only 1 year after Thomas Starzl's historic first attempt in the world at human liver transplantation in Denver, CO.…”
Section: History Of Liver Transplantation In Asiamentioning
confidence: 99%
“…An international survey showed that from 1995 to 2005, the annual number of LDLT procedures in other parts of Asia increased more than 10-fold, whereas rates for liver transplantation using deceased donors remained almost static for more than a decade. 1 On average, LDLT was used for nearly 90% of liver transplants in most parts of Asia. Japan is the most extreme example because of its belated brain death legislation, but the latest data from the Japanese Liver Transplantation Registry 3 show that the proportion of deceased donor liver transplantation increased to nearly 10% in 2011.…”
Section: Current Status Of Liver Transplantation In Asiamentioning
confidence: 99%